Overview of the Incidence of Depression in Patients Undergoing Hemodialysis at Dr. Moewardi Surakarta Hospital - Hermawati; Ika Silvitasari; Wahyuni (STIKES Ngesti Waluyo, 2022)
Chronic renal failure or chronic kidney disease (CKD) is a global public health problem with the prevalence and incidence of kidney failure increasing. Changes in the quality of life in patients with Chronic Kidney Failure will cause depression. Chronic kidney failure patients with depression will experience emotional disturbances, prolonged emotional related mental processes (thought patterns, feelings, activities), negative personal thoughts, decreased mood, loss of motivation, slow in thinking and decreased activity. The aim of this study was to describe the incidence of depression in patients undergoing hemodialysis. The type of research used in this research is descriptive correlation with a survey approach. Respondents undergoing hemodialysis who experience mild depression will lose interest, enthusiasm, reduced energy and also get tired easily. This will lead to reduced self-esteem and self-confidence, decreased activity, concentration and attention. The conclusion from the results of this study is that the majority of chronic kidney failure patients undergoing hemodialysis experience mild depression, namely 48 people (80%) and 12 people (20%) experiencing moderate depression. There was none of the respondents who experienced major depression and none who did not experience depression.